Effects of preventive nursing based on quantitative evaluation on psychological state and maternal–infant outcome in patients with gestational diabetes mellitus. (31st December 2023) - Li, Hailian; Li, Haixiang; Li, Xiaodan; Wang, Jing; Wang, Pan; Zhao, Mingxia
Abstract: Objective: To explore the effects of preventive nursing based on quantitative evaluation on psychological state and maternal–infant outcome in patients with gestational diabetes mellitus (GDM), further, to provide a theoretical basis for the effective management of GDM patients in clinical work. Methods: From 1 February 2020 to 1 January 2021, 118 patients with GDM presenting to our hospital were included in this retrospective cohort study. According to the type of nursing care, patients were divided into study group and control groups. The study group consisted of 59 GDM patients who were given quantitative evaluation-based preventive nursing care. The control group included 59 GDM patients who were given routine nursing care. Outcome indicators included blood glucose level, degree of social support, resilience, coping style, and maternal–infant outcomes. Results: There was no significant difference between two groups in other baseline clinical characteristics ( p > .05). After the intervention, fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), and 2 h postprandial blood glucose (2hPBG) levels were significantly lower in the study group than that in the control group ( p < .05). The scores of objective support, subjective support, and social support utilization in the study group were significantly higher than those in the control group after intervention ( p < .05). The scores of optimisms, self-strengthening and tenacity in the study group were significantly less than those in the control group ( p < .05). The study group confrontation score was significantly higher, and the avoidance and acceptance scores were significantly lower, compared with the control group ( p < .05). The maternal–infant outcome showed that the proportions of cesarean delivery, pregnancy-induced hypertension, polyhydramnios, premature delivery, hyperbilirubinemia, and neonatal hypoglycemia in the study group were significantly lower than those in the control group ( p < .05). There was no significant difference in the incidence of postpartum hemorrhage and neonatal 5-min Apgar score between the two groups ( p > .05). Conclusions: In conclusion, preventive nursing based on quantitative assessment can effectively control the blood glucose level of GDM patients, improve their degree of social support, resilience, coping style, and maternal–infant outcomes, which is worthy of clinical application.